Pengaruh Brand image dan Nutrition label terhadap Keputusan Pembelian dengan Gaya Hidup Sehat Sebagai Variabel Moderasi - Gusti Ayu Sinta Jelantik; Ni Made Wulandari Kusumadewi (Universitas 17 Agustus 1945, 2024)
Consumer purchasing decisions are one of the most crucial aspects for companies, because purchasing decisions can affect revenue, business growth, reputation, competition in the market, operational efficiency, product innovation, and customer loyalty. There are several factors that influence purchasing decisions, including brand image and nutrition label. This study aims to examine the effect of brand image and nutrition label on purchasing decisions with a healthy lifestyle as a moderating variable. The sample used in this study was 100 respondents. The sampling method used in this study was purposive sampling method. Data collection was carried out through distributing questionnaires online via google form and offline distribution where respondents received and answered on a questionnaire sheet. The data analysis technique used in this research is Moderated Regression Analysis. The results of this study indicate that brand image and nutrition label partially have a significant effect on Fitbar purchasing decisions in Denpasar City. Then, healthy lifestyle moderates brand image and nutrition label partially on Fitbar purchasing decisions in Denpasar City.